Register Classification by Timbre - Uwe Ligges; Christoph Reuter; Claus Weihs (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2004)
The aim of this analysis is the demonstration that the high and the low musical register (Soprano, Alto vs. Tenor, Bass) can be identified by timbre, i.e. after pitch information is eliminated from the spectrum. This is achieved by means of pitch free characteristics of spectral densities of voices and instruments, namely by means of masses and widths of peaks of the first 13 partials (cp. Weihs and Ligges (2003b)). Different analyses based on the tones in the classical song ?Tochter Zion? composed by G.F. Händel are presented. Results are very promising. E.g., if the characteristics are averaged over all tones, then female and male singers can be easily distinguished without any error (prediction error of 0%)! Moreover, stepwise linear discriminant analysis can be used to separate even the females together with 28 high instruments (?playing? the Alto version of the song) from the males together with 20 low instruments (playing the Bass version) with a prediction error of 4%. Also, individual tones are analysed, and the statistical results are discussed and interpreted from acoustics point of view.
Keywords: 519